Groundwork : between landscape and architecture - Balmori, Diana. (Monacelli Press, 2025)
Human/nature: wilderness and the landscape/architecture divide / Joel Sanders -- Across the divide: between nature and culture / Diana Balmori -- Topography : Cairo Expo City / Zaha Hadid Architects ; Island City Central Park Grin Grin / Toyo Ito & Associates ; Urban garden in Nørresundby / SLA ; City of Culture of Galicia / Eisenman Architects ; Seattle Art Museum Olympic Sculpture Park / Weiss, Manfredi ; Sigirino Depot / Atelier Girot ; Lycée Jean Moulin / Duncan Lewis Scape Architecture with OFF Architecture ; Symbiosis'hood / R & Sie(n) ; Petter Dass Museum / Snøhetta -- Ecology : I'm lost in Paris / R & Sie(n) ; Sportplaza Mercator / VenhoevenCS ; Eco-Pod: Pre-cycled modular bioreactor / Höweler + Yoon Architecture and Squared Design Lab ; Convective apartments / Philippe Rahn Architectes ; Stockholm Energy Pavilion / Habiter Autrement ; Turistroute in Eggum / Snøhetta ; Urban Outfitters Headquarters / D.I.R.T. Studio ; NYC 2012 Olympic Equestrian Facility / Balmori Associates and Joel Sanders Architect ; Parque Atlántico / Batlle i Roig Arquitectes -- Biocomputation : Grotto concept / Aranda, Lasch ; North Side Copse House / EcoLogicStudio ; New Czech National Library / OCEAN NORTH and Scheffler + Partner ; Yeosu Oceanic Pavilion / EMERGENT Tom Wiscombe with KOKKUGIA ; Amphibious architecture / Living Architecture Lab at Columbia University GSAPP; Environmental Health Clinic at NYU ; Local Code: real estates / Nicholas de Monchaux ; DUNE: Arenaceous anti-desertification architecture / Magnus Larsson.